Ultra‐Permeable Single‐Walled Carbon Nanotube Membranes with Exceptional Performance at Scale. Issue 24 (9th November 2020) - Jue, Melinda L.; Buchsbaum, Steven F.; Chen, Chiatai; Park, Sei Jin; Meshot, Eric R.; Wu, Kuang Jen J.; Fornasiero, Francesco
Abstract: Enhanced fluid transport in single‐walled carbon nanotubes (SWCNTs) promises to enable major advancements in many membrane applications, from efficient water purification to next‐generation protective garments. Practical realization of these advancements is hampered by the challenges of fabricating large‐area, defect‐free membranes containing a high density of open, small diameter SWCNT pores. Here, large‐scale (≈60 cm 2 ) nanocomposite membranes comprising of an ultrahigh density (1.89 × 10 12  tubes cm −2 ) of 1.7 nm SWCNTs as sole transport pathways are demonstrated. Complete opening of all conducting nanotubes in the composite enables unprecedented accuracy in quantifying the enhancement of pressure‐driven transport for both gases (>290× Knudsen prediction) and liquids (6100× no‐slip Hagen–Poiseuille prediction). Achieved water permeances (>200 L m −2 h −1 bar −1 ) greatly exceed those of state‐of‐the‐art commercial nano‐ and ultrafiltration membranes of similar pore size. Fabricated membranes reject nanometer‐sized molecules, permit fractionation of dyes from concentrated salt solutions, and exhibit excellent chemical resistance. Altogether, these SWCNT membranes offer new opportunities for energy‐efficient nano‐ and ultrafiltration processes in chemically demanding environments. Abstract : Membranes with an ultrahigh density of open single‐walled carbon nanotubes (SWCNT) as the sole transport pathways are demonstrated at the unmatched scale of 60 cm 2 . These membranes enable accurate quantification of the massive SWCNT amplification of pressure‐driven flow, outperform state‐of‐the‐art commercial membranes with similar pore diameters, and display excellent oxidative resistance.